Utility of Using the Montreal Cognitive Assessment (MoCA) as a Screening Tool for HIV-Associated Neurocognitive Disorders (HAND) In Multi-Ethnic Malaysia - Mukherjee, Trena; Sakthivel, Rishanantini; Ho, Yen Fong; McStea, Megan; Chong, Meng Li; Omar, Sharifah Faridah Syed; Chin, Ai-Vyrn; Kamaruzzaman, Shahrul Bahyah; Kamarulzaman, Adeeba; Rajasuriar, Reena; Cysique, Lucette A. (Springer, 2018)
This study determines the optimal cut-off scores for the Montreal Cognitive Assessment (MoCA) to detect HIV-associated neurocognitive disorders (HAND) in a multi-ethnic Malaysian HIV-positive cohort by developing demographically corrected normative standards among 283 HIV-negative community-based controls with overlapping demographic characteristics. The norms (corrected for age, sex, education, ethnicity) were applied to 342 HIV-positive virally suppressed individuals on cART. Impairment rates were classified using the Global Deficit Score (GDS ≥.5) method. The MoCA was also scored according to the recommended cut-off of ≤ 26, and functional decline was applied to both impairment definitions to classify HAND per the Frascati criteria. The ≤ 26 cut-off considerably overestimated cognitive impairment in both samples (59.4% HIV-negative; 69.3% HIV-positive). In contrast, corrected scores yielded impairment rates consistent with what has been reported internationally in virally suppressed cohorts (23.4% with 83.3% mild impairment, 16.7% moderate impairment). A supplemental file allowing the computation of corrected MoCA scores and impairment status is included.